2018
DOI: 10.1063/1.5022916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rainfall infiltration into unsaturated soil using soil column

Abstract: Abstract. Rainfall especially in tropical region caused infiltration to the soil slope. The infiltration may change pore water pressure or matric suction of the soil. The event of rainfall infiltration into soil is a complex mechanism. Therefore, the main objectives of this research paper is to study the influence of rainfall intensity and duration that changed pore water pressure to soil. There are two types of soils used in this study; forest soil and kaolin. Soil column apparatus is used for experiments. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…This result revealed that high intensity rainfall led to low soil permeability. This was mainly because the gas in the bottom soil pores cannot be discharged in time due to the rapid infiltration of water, thereby forming pore gas pressure for water infiltration (Ibrahim, Mukhlisin, & Jaafar, ; Prunty & Bell, ; Xue, Tong, Hao, & Wang, ). Therefore, a high rainfall intensity did not result in a significant increase in volumetric water contents at lower soil depths.…”
Section: Discussionmentioning
confidence: 99%
“…This result revealed that high intensity rainfall led to low soil permeability. This was mainly because the gas in the bottom soil pores cannot be discharged in time due to the rapid infiltration of water, thereby forming pore gas pressure for water infiltration (Ibrahim, Mukhlisin, & Jaafar, ; Prunty & Bell, ; Xue, Tong, Hao, & Wang, ). Therefore, a high rainfall intensity did not result in a significant increase in volumetric water contents at lower soil depths.…”
Section: Discussionmentioning
confidence: 99%
“…Top-layer soils have reduced matric suction due to rainfall infiltration [4], which in turn reduces soil strength. The mechanism of rainfall infiltration is complex due to the high nonlinearity of soil water characteristics and soil permeability [5].…”
Section: Field Infiltration Monitoringmentioning
confidence: 99%
“…Porém, alguns destes estudos que tem sido conduzido em laboratório, utilizaram tensiômetros e simulações de chuva em colunas de acrílico contendo um único tipo de solo, visando o estudo das características hidrodinâmicas dos solos (LEIJ et al, 2006;IBRAHIM et al, 2014). Contudo Leij et al (2006) deixa claro que o uso de colunas homogêneas, as quais são compostas por um único tipo de solo, são utilizadas, basicamente, nas modelagens para pequenas profundidades (0-2000 mm).…”
Section: Introductionunclassified